Ecology, Technology and Culture. Essays in Environmental Philosophy - Zweers W. Wim; Boersema J. Jan (Cambridge, The White Horse Press, 1994)
Ecology, Technology and Culture is a slightly adapted translation of a collection of essays originally published in Dutch. The book deals with current environmental issues debated in western societies, although the philosophical realm of the essays is thoroughly European. It offers a variety of perspectives on the environmental crisis, in some ways distinct from Anglo-American scholarship, and ranging from historical, theological and hermeneutic viewpoints to scientific, political, economic and technological issues. The introductory article, 'A Framework for Environmental Philosophy', oudines the development and the current situation of the field in the Netherlands. We should like to thank Miriam Hall for her assistance with the translation, and to acknowledge substantial financial support from members of the Dutch Association for Environmental Philosophy and the Centre for Applied Ethics at Erasmus University, Rotterdam.